INCIDENCE OF DIABETIC GANGRENE IN PATIENTS WITH TYPE 2 DIABETES MELITUS AT ROYAL PRIMA HOSPITAL - Jaskaran Dhillon; Erwin Sopacua; Erny Tandanu (Universitas Negeri Gorontalo, 2022)
Diabetes is a metabolic disorder classified as chronic hyperglycemia. It is disorder of protein, carbohydrate and fat metabolism, which can result from dysfunction in insulin secretion and the mechanisms of insulin. An estimated 366 million people suffered from DM in 2011Diabetic gangrene arises from complication of DM. It results from infection or wound inflammatory process in advanced phase caused by either less intensive care or degenerative changes. The objective of this study is to assess the incidence of diabetic gangrene in patients with type 2 diabetes mellitus at Royal Prima Hospital This type of research is a retrospective study. The sample of this study was conducted at the Royal Prima Hospital for the period 1 January 2020 - 31 December 2020. The number of respondents used purposive sampling method, with inclusion and exclusion criteria. Data collection in this study is non-probability sampling with purposive sampling technique. The highest proportion of diabetic gangrene sufferers in type 2 diabetes mellitus patients was found at the age of 51-60 years with percentage (54.4%), while the lowest proportion was at age 40 years with a percentage (3.5%), and obtained age 40-50 years with a percentage (19.3%) and 60 years with percentage (22.8%). The proportion of patients with diabetic gangrene in type 2 diabetes mellitus patients was male (63.2%) more than female (36, 8%). The highest proportion of diabetic gangrene sufferers in type 2 diabetes mellitus patients with KGD ranges from 200-300 mg/dl (52.6%) and the lowest is 100 mg/dl (1%)